Ideomotor Action: Evidence for Automaticity in Learning, but Not Execution - Sun, Dan; Custers, Ruud; Marien, Hans; Aarts, Henk (Frontiers in Psychology, 2020)
Human habits are widely assumed to result from stimulus-response (S-R) associations that are formed if one frequently and consistently does the same thing in the same situation. According to Ideomotor Theory, a distinct but similar process could lead to response-outcome (R-O) associations if responses frequently and consistently produce the same outcomes. This process is assumed to occur spontaneously, and because these associations can operate in a bidirectional manner, merely perceiving or thinking of an outcome should automatically activate the associated action. In the current paper we test this automaticity feature of ideomotor learning. In four experiments, participants completed the same learning phase in which they could acquire associations, and were either explicitly informed about the contingency between actions and outcomes, or not. Automatic action selection and initiation were investigated using a free-choice task in Experiment 1 and forced-choice tasks in Experiment 2, 3a and 3b. An ideomotor effect was only obtained in the free-choice, but not convincingly in the forced-choice tasks. Together, this suggests that action-outcome relations can be learned spontaneously, but that there may be limits to the automaticity of the ideomotor effect.